EFIKASI DAN KESEJAHTERAAN PSIKOLOGIS PADA GURU SMP - DEASYANTI DEASYANTI; AMALINA MAFAZI (Journal of Research and Measurement in Psychology, 2016)
The purpose of this study was to know the relations between teacher efficacy with psychological well-being among junior high school teacher with survey method and adapted psychological scale to collect the data which is Ryff’s Psychological Well-being Scale from Carol D. Ryff (1989) with reliability is 0.95 and The Teacher’s Sense of Efficacy Scale (TSES) from Tschannen-Moran and Anita Woolfolk Hoy (2001) with reliability is 0.80. The psychological scale has been given to 88 samples of respondent which is junior high school teacher with cluster random sampling technique. Researcher also used analytical correlation and Winsteps 3.73 also SPSS 16.0 version as application for testing the hypothesis of this research. The result of correlations analysis shown that r value 0.213 and probability score (sig) is 0.047. Conclusion this research result there is significant relationship between teacher efficacy with psychological well-being among junior high school teacher.